People People : Social Capital and the Labor-Market Outcomes of Underrepresented Groups - Lex Borghans; Bas ter Weel; Bruce A. Weinberg (Institute for the Study of Labor (IZA), 2005)
Despite indications that interpersonal interactions are important for understanding individual labor-market outcomes and have become more important over the last decades, there is little analysis by economists. This paper shows that interpersonal interactions are important determinants of labor-market outcomes, including occupations and wages. We show that technological and organizational changes have increased the importance of interpersonal interactions in the workplace. We particularly focus on how the increased importance of interpersonal interactions has affected the labor-market outcomes of underrepresented groups. We show that the acceleration in the rate of increase in the importance of interpersonal interactions between the late 1970s and early 1990s can help explain why women?s wages increased more rapidly, while the wages of blacks grew more slowly over these years relative to earlier years.
Keywords: J21; J16; J31; J24; 330; interpersonal interactions; wage level and structure; economics of minorities and races and gender; social capital; Ethnische Gruppe; Frauenerwerbstätigkeit; Lohndifferenzierung; Social Capital; Soziale Beziehungen; Technischer Fortschritt; Berufliche Integration; Schätzung; Vereinigte Staaten